PEMETAAN BANGUNAN BERIJIN DAN TIDAK BERIJIN SEBAGAI UPAYA SINKRONISASI PEMANFAATAN RUANG KABUPATEN KUTAI KARTANEGARA - Titin Widiya Permata Sari; Fadhilatus Shoimah (PANGRIPTA, 2023)
There are many violations of Building Permits in Kutai Kartanegara Regency, especially in urban areas, Tenggarong District. In addition, several existing land uses in the urban area of ​​Tenggarong District need to be identified in the actual field which can be used as a basis for future spatial planning processes. This study aims to map buildings that already have a Building Permit and those that do not have a Building Permit. The data analysis process is carried out on the Arc GIS software. The analysis is carried out using digitization, query, and overlay operations for the manipulation of spatial features. The results of building mapping that has been carried out in the research area, it was found that 1) Residential buildings that have a Building Permit are 270 buildings or 0.94% of the total residential buildings in the planning area; 2) Business entity buildings that have a Building Permit of 2.5% or 715 buildings of the total business entity buildings in the planning area; 3) Buildings that have a Building Permit of 3.44% or 985 buildings of the total buildings in the planning area; 4) Buildings that do not have a Building Permit are 96.56% or 27,616 buildings of the total buildings in the planning area.